Comparison between boost and positive output super lift Luo converters to improve the performance of photovoltaic system - Ream Mohammed Jassim; Kadhim H. Hassan; Issa Ahmed Abed (Institute of Advanced Engineering and Science, 2022)
Employment DC-DC switching power converters in many different areas become is very important. In this paper, three different models of the photovoltaic solar module were proposed in order to designing, implementation, and simulated them in MATLAB/Simulink with the boost converter circuit first and then with the positive output super lift Luo (POSLL) converter circuit again. A comparison was made between the two circuits, as well as a theoretical and simulation values were made and compared between them (in the same standard conditions) for each of these selected models. So as to improving solar system performance and clarify the functions played by POSLL in power electronic circuits.